The Impact of Climate Change on Agricultural Operations: an Applied Study on Crops in the Jordan Valley - Alalwan, Ahmad Mohammad Hamdan (Newinera Publisher, 2022)
Climate change, as manifested through its multifaceted dimensions encompassing economic, social, and security effects, on agricultural activities within the Jordan Valley region. The research sample encompassed a group of 9000 agricultural practitioners residing in the Jordan Valley region. Employing the well-established Morgan model, a representative subset of 368 individuals was selected through a random sampling technique. The questionnaires were disseminated among the participants of the study, resulting in the retrieval of a total of 350 questionnaires. Upon careful examination, it was determined that 340 of these questionnaires were deemed valid and suitable for analysis. A meticulously crafted survey instrument was devised to systematically gather firsthand information. The research employed a quantitative (descriptive analytical) methodology to examine the data and evaluate hypotheses by employing suitable statistical techniques available in the Statistical Package for Social Sciences (SPSS). The findings of the study indicate a noteworthy and statistically significant relationship between climate change and agricultural operations. The analysis yielded a substantial coefficient of determination (R²=68.5%), suggesting that approximately 68.5% of the changes observed in agricultural operations can be attributed to the influence of climate change. The study proposes a strategic approach to enhance farmers' understanding of the indirect impact of climate change on various economic sectors, including manufacturing, energy production, transportation, and other services. This can be achieved through the implementation of educational initiatives, such as seminars and awareness sessions, which actively engage farmers in the learning process.